Կրոնական թեմատիկայի արտացոլումը Միհրի Հաթունի ստեղծագործություններում - Մարիամ Մելքոնյան (ՀՀ ԳԱԱ հրատ.)
Проблема Бога, сотворения мира и человека постоянно присутствовала в придворной литературе Дивана вследствие влияния на нее догматическихтечений ислама, в особенности суфизма. Правители, рассматривающие мир с религиозной точки зрения, пытались найти ответы на вопросы о его возникновении и создании. В XV-XVI веках османские поэтессы, в частности Михри Хатун, некоторым образом также пытались обратиться к этой теме.The issues about the existence of God, the creation of human beings and the world have always been discussed in Divan’s literature under the influence of Islamic dogmatic movements, particularly Sufism. The poets who perceive the world from the religious point of view try to find reasons why the world was created and some answers to the questions connected with the beginning of human history. In the XV-XVI centuries even Ottoman women writers made some attempts to address these topics and one of them was Mihri Hatun.
Keywords: Language and Literature